Proyecto de factibilidad para la creación de una empresa de servicios de limpieza para hogares en el cantón Lago Agrio, provincia de Sucumbíos - Cabezas Cabezas, Digna Isabel (2017)
The general objective of the present investigation is to determine the feasibility of the proposal of creation of a company of cleaning of homes in the canton Lago Agrio of the province of Sucumbíos in which were used the different methods and techniques that the investigation allows to realize, As the deductive method the same that allowed the comparison of facts investigated and compare them with the concepts, the inductive method facilitated to know the particularities of the market as the sample size, with general data and real local population potential demand, Real, effective and unsatisfied demand and the statistical method instead was used to measure the results obtained from the surveys. The market study carried out in the present project has a sample of 379 families within the canton Lago Agrio; Tabulated the surveys have been analyzed and inferred the results to then carry out the study and analysis of the market, determining the potential demand of the same. The unsatisfied demand reflects the potential market that exists in the canton Lago Agrio of the province of Sucumbíos for the aforementioned company with the following results: for the base year of useful life of the project the unsatisfied demand is 61,373 services, the installed capacity of the Project determines that the company will be in the capacity of the percentage that it has to offer the services, of which 8.90% of the unsatisfied demand is determined. Next, the project engineering is developed, determining the process diagrams, operational and management characteristics, technical requirements such as equipment, furniture and appliances. Likewise, an administrative study was carried out determining itself as a Limited Liability Company and with the functional organic structure, function manuals, organizational charts; Which served as a guideline to implement a good organization, since the following personnel would be counted: Manager, Secretary, accountant, Supervisor and Cleaning Operators. The project reaches an investment of 54,648.17 dollars and will be financed with a contribution of the partners 45.10% of the total of the investment that corresponds to 24.648,17 dollars and a loan that will maintain the project with the National Financial Corporation the 54.90% that Corresponds to $ 30,000 to 10 year term at 15.20% annual interest. The financial evaluation presents the following results: According to the NPV of the present project it has a positive result of 84,045.70 dollars, indicating that the project or investment is feasible. For the present project, the TIR is 52.98%, this value being satisfactory to carry out the project, the time that would be required to recover the original investment would be 10 months and 7 days, for the present project, the sensitivity values are less than one, Therefore, changes in costs and revenues increased by 13.86% and decreased by 10.67%, respectively, ie the project is not sensitive to these changes.